Wellbeing during a pandemic: An empirical research examining autonomy, work-family conflict and informational support among SME employees - Zakhem, Najib Bou; Farmanesh, Panteha; Zargar, Pouya; Kassar, Abdulnasser (Frontiers in Psychology, 2022)
Individuals working in different industries were forced to change their work environments to their homes and quickly cope with technical and social changes not experienced before the occurrence of COVID-19 pandemic. This led to blurred boundaries between work and family roles, diminishing performance and wellbeing. Within the scope of the Research Topic “Workplace effects of COVID-19 on employees,” this research emphasizes on the positive impact of job autonomy provided by employers in reducing work-family conflicts. Moreover, the effect of work-family conflict on employees’ performance and wellbeing is analyzed. Furthermore, informational support is examined regarding its moderating effect to mitigate work-family conflicts and enhance wellbeing. A survey was administered among employees of small-medium enterprises in Lebanon, through purposive and convenience sampling with 198 participants. The data was analyzed using PLS-SEM, and the results show that job autonomy reduces work-family conflict. This in turn improves performance and wellbeing as individuals have more control on their tasks. Furthermore, informational support provided to the employees serves as a buffer between work-family conflict and wellbeing. These results can be beneficial for managers of small and medium enterprises, seeking to enhance the performance and wellbeing of their employees in the era of the pandemic. Similarly, scholars can benefit from theoretical premises of current study and the potential pathways for future analyses.